Determining asymmetry using specific unilateral tests in young basketball players - Dukaric, V.; Rupcic, T.; Li, F.; Cigrovski, V.; Knjaz, D. (SportLogia, 2022)
Defining the differences between the dominant (D) and non-dominant (ND) leg is one of the ways to determine the asymmetry between the extremities and thus the risk of injury. The aim of this research is to determine the differences in specific unilateral tests in young male and female basketball players. The sample consisted of 17 female basketball players (average height 177.96 ± 6.38 cm; average weight 69.53 ± 8.00 kg and age 15.50 ± 0.96 yr.) and 34 male basketball players (average height 194.29 ± 7.52 cm; average weight 83.66 ± 9.66 kg and age 15.40 ± 1.28 yr.) of the cadet and junior national teams. Tests were used to assess the explosive power of the lower extremities: high jump with D and ND leg take-off with arm swing (S_vis_jedn_L; S_vis_jedn_D), basketball two-step with D and ND leg take-off (Dvokorak_L, Dvokorak_D) and Drift protocol consisting of 5 consecutive unilateral jumps in place (Drift_L, Drift_D). The tests S_vis_jedn (p = 0.02) and Dvokorak (p = 0.03) showed statistically significant differences with an error of p?0.05 in the group of male basketball players. Significant differences were found in female basketball players in the test S_vis_jedn (p = 0.03). In other tests, there are no significant differences between jumps with D and ND leg take-off. The presented results indicate differences between the extremities and represent the basis for the correction of the training plan and program. The methodology in this paper is simple to implement and analyse and is aimed at imitating situational conditions.